2021
DOI: 10.1038/s41467-021-23796-4
|View full text |Cite
|
Sign up to set email alerts
|

Large variation in anti-SARS-CoV-2 antibody prevalence among essential workers in Geneva, Switzerland

Abstract: Limited data exist on SARS-CoV-2 infection rates across sectors and occupations, hindering our ability to make rational policy, including vaccination prioritization, to protect workers and limit SARS-CoV-2 spread. Here, we present results from our SEROCoV-WORK + study, a serosurvey of workers recruited after the first wave of the COVID-19 pandemic in Geneva, Switzerland. We tested workers (May 18—September 18, 2020) from 16 sectors and 32 occupations for anti-SARS-CoV-2 IgG antibodies. Of 10,513 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
2
33
0
2
Order By: Relevance
“…In addition, very few, if any, longitudinal cohort studies on the SARS-CoV-2 seropositivity have been performed after well-documented outbreaks in private factories or companies where the risk of virus spread is lower and the possibilities for periodic monitoring of the humoral immune response are more challenging as compared to hospitals. A serosurvey of workers recruited after the first wave of the COVID-19 pandemic from 16 sectors and 32 occupations showed that seropositivity rates varied widely across sectors and occupations, reflecting a higher exposure in nursing home and healthcare sectors [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, very few, if any, longitudinal cohort studies on the SARS-CoV-2 seropositivity have been performed after well-documented outbreaks in private factories or companies where the risk of virus spread is lower and the possibilities for periodic monitoring of the humoral immune response are more challenging as compared to hospitals. A serosurvey of workers recruited after the first wave of the COVID-19 pandemic from 16 sectors and 32 occupations showed that seropositivity rates varied widely across sectors and occupations, reflecting a higher exposure in nursing home and healthcare sectors [22].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were selected from a serosurvey cohort recruiting essential workers between May and September 2020 in Geneva, Switzerland. 6 Data of SARS-CoV-2 infections were extracted from a centralized state registry and linked to each participant, as previously described. 2 Workers were categorised into three pre-defined groups, according to their exposure risk: occupations likely requiring sustained physical proximity to other individuals (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Essential workers were unequally affected in the early phases of the pandemic, with healthcare workers (HCW) being at higher risk of contracting infections, 4 5 and a wide variability in seropositivity across occupations. 6 Close contact and inadequate personal protective equipment have been identified as risk factors, 7 generating a large deployment of social distancing and barrier measures. Despite this, a second pandemic surge affected most countries worldwide, taking place at the end of 2020 in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were selected from a serosurvey cohort recruiting essential workers between May and September 2020 in Geneva, Switzerland. 6 Data of SARS-CoV-2 infections were extracted from a centralised state registry and linked to each participant, as previously described. 2 Workers were categorised into three predefined groups, according to their exposure risk: occupations likely requiring sustained physical proximity to other individuals (eg, HCW, childcare and social workers), occupations involving regular brief contact (eg, pharmacists, taxi drivers, grocery workers) and other essential occupations (eg, farmers, managers and health researchers) (online supplemental table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Essential workers were unequally affected in the early phases of the pandemic, with HCWs being at higher risk of contracting infections, 4 5 and a wide variability in seropositivity across occupations. 6 Close contact and inadequate personal protective equipment have been identified as risk factors, 7 generating a large deployment of social distancing and barrier measures. Despite this, a second pandemic surge affected most countries worldwide, taking place at the end of 2020 in Switzerland.…”
Section: Introductionmentioning
confidence: 99%